2020
DOI: 10.1007/s43076-020-00037-z
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Relationship and Partner Schemas: Concepts Associated with a Positive Valence

Abstract: This study identifies concepts associated with positive valence of romantic relationship and partner, in order to characterize the schemas about these two phenomena. Participants (N = 158, 134 women) were asked to write about the positive aspects of their relationship and their partner. These reports were subjected to lexical and content analysis. Nineteen categories emerged, related to the concepts that compose the relationship schema, and 21 others related to the partner. Words and categories most frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Also, Sex and Longing distinguished this love from others. Londero‐Santos et al (2020), investigating partner schemas in Brazil, found concepts quite similar to those found in this research. Similar categories representing romantic love were reported in different countries, like Ireland and Lithuania (Manoharan & Munck, 2017), Canada (Fehr, 1994), and New Zealand (Fitness & Fletcher, 1993).…”
Section: Discussionsupporting
confidence: 87%
“…Also, Sex and Longing distinguished this love from others. Londero‐Santos et al (2020), investigating partner schemas in Brazil, found concepts quite similar to those found in this research. Similar categories representing romantic love were reported in different countries, like Ireland and Lithuania (Manoharan & Munck, 2017), Canada (Fehr, 1994), and New Zealand (Fitness & Fletcher, 1993).…”
Section: Discussionsupporting
confidence: 87%
“…Specific investments in a relationship comprise contributions that “individuals bring to a relationship or do in a relationship that influences their exchange value to the partner” (Ellis, 1998, p. 384). In a recent study conducted with respondents in Brazil, Londero‐Santos et al (2020a, 2020b) found that individuals whose schema of their couple relationship held concepts of affection, respect, and dialogue with their romantic partner experienced a higher level of relationship satisfaction when compared with individuals whose schemas did not include these concepts. This seems to indicate the importance of such concepts and types of symbolic investment in relationships in predicting relationship satisfaction.…”
Section: The Impact Of Relationship Investment Tactics On Relationshi...mentioning
confidence: 99%
“…5,11,12 Sexual life provides adjustment, mutual satisfaction, consensus, and emotional expression about the relationships of the partners. 13,14 For this reason, it is important in meeting the need for intimacy and understanding their relationships. This situation makes it a priority to continue sexual life in individuals with SCI.…”
Section: Introductionmentioning
confidence: 99%